تأثير التسميد العضوي والمعدني ونظم الحراثة في بعض صفات الإنتاج لمحصول القطن (السلالة 124) في ظروف منطقة الغاب - عبد العزيز محمد; السلتي محمد; زيـود عمار (Latakia University Journal -Biological Sciences Series, 2019)
أنجز البحث خلال الموسمين الزراعيين 2009-2010 في مركز البحوث العلمية الزراعية في الغاب لدراسة تأثير ثلاثة نظم للحراثة (1-حراثة سطحية غير قلابة 0-20 سم, 2-حراثة متوسطة قلابة 0-30 سم،3-حراثة عميقة قلابة 0-40 سم) ومعدلين للتسميد العضوي بروث الغنم (20، 30) طن/هـ وتسميد معدني(شاهد المزارع) في بعض مكونات الغلة لمحصول القطن (السلالة 124)، وصممت التجربة بطريقة القطاعات المنشقة بثلاثة مكررات وبينت الدراسة تفوق التسميد العضوي (30) طن/هـ معنوياً على التسميد المعدني والتسميد العضوي (20) طن/هـ في الصفات المدروسة، ووصلت نسبة الزيادة في الإنتاجية كغ/هـ إلى( 11.02 ، 6.11)% على التوالي في الموسم الأول وإلى ( 12.87، 6.43 )% في الموسم الثاني، وتفوقت الحراثة العميقة معنوياً على الحراثة السطحية والمتوسطة في الصفات المدروسة، ووصلت نسبة الزيادة في الإنتاجية كغ/هـ إلى(34.92 ، 11.22 )% في الموسم الأول على التوالي و(25.25، 9.78)% في الموسم الثاني، وأعطى التفاعل بين معاملات التسميد ومعاملات نظم الحراثة أفضل القيم عند الحراثة العميقة والتسميد العضوي (30) طن/هـ. This research was carried out during 2009 and 2010 in AI-Ghab Research Center to study the effect of three tillage systems: 1 - No tipper surface plowing 0-20 cm, 2 - Tipper medium plowing 0 -30 cm, 3 - Tipper deep plowing 0 -40 cm); the effect of two rates of organic fertilization by sheep manure (20,30) ton/ha; and the effect of mineral fertilization (farmer control) on some yield components of cotton crop (strain 124). The experiment was laid out in split-plot design (SPD) using three replications. The study showed a significant increase in the organic fertilization (30 ton/ha) in studied characteristics compared to mineral fertilization and organic fertilization (20 ton/ha), The rate of increase in productivity kg / h grew up (6.11 ، 11.02) %in the first season and (6.43 ، 12.87) % in the second season respectively. The tipper deep tillage increased significantly in studied characteristics compared to Tipper plowing surface and tipper medium plowing, The rate of increase in productivity kg / h grew up (11.22،34.92)% in the first season and (25.25, 9.78)% in the second season respectively. The interaction between treatments of fertilization and tillage systems resulted in organic fertilization(30 ton/ha) and Tipper deep plowing (0 -40 cm).